HUBUNGAN PENGETAHUAN DAN SIKAP ORANG TUA DENGAN PERILAKU STIMULASI TUMBUH KEMBANG ANAK DI POSYANDU RINDU SEJAHTERA DESA PENFUI TIMUR - Matje Meriaty Huru; Mariana Ngundju Awang; Agustina Abuk Seran; Melinda Rosita Wariyaka; Ni Luh Made Diah Putri Anggaraeningsih; Maria Florentina Nining Kosad; Nurlaelah Al Tadom; Nabila Nurul Ilmi (Rena Cipta Mandiri, 2025)
Early childhood (0–6 years) is a critical period during which children's brain development occurs rapidly, reaching approximately 80% of adult capacity by the age of 3 years. This development is greatly influenced by stimulation from an early age, both cognitively, language, social-emotional, and motoric. Early stimulation has been proven to play a major role in maximizing children's development potential, preventing delays, and increasing readiness to enter primary education. Children receiving regular stimulation have higher cognitive development scores and a lower risk of delays. This research aims to determine the relationship between parental knowledge and attitudes and the behavior of stimulating children's growth and development at Posyandu Rindu Sejahtera, East Penfui Village. This research uses a quantitative design with a correlational analytical approach. The population in this study were all parents who had children aged 0–5 years and were registered as active participants at Posyandu Rindu Sejahtera, as many as 52 people, with a total population sample. Data analysis uses univariate analysis to describe the frequency distribution of each variable, and bivariate analysis using the Chi-Square test. The results of the research show that there is a significant relationship between parental knowledge and attitudes and the behavior of stimulating children's growth and development.